Learning Strategies at SD Muhammadiyah 1 Candi during the Covid 19 Pandemic - Arizkylia Yoka Putri; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This Study aims to provide an overview of the trategies implemented by SD Muhammadiyah 1 Candi in the learning process during the Covid 19 pandemic. The method used in this research is descriptive qualitative method. The data collection techniques in this study were trough interviewes, documentation and observation. During the covid 19 pandemic, SD Muhammadiyah 1 Candi implemented an online learning policy, in accordane with the instructions issued by the minister of education and culture Nadiem Makarim through Circular Number 4 of 2020 concerning Implementation of Educational Policies in the emergency period of the spread of the Corona virus. Online learning is carried out in order to reduce the spread of covid-19. During the implementation of online learning, SD Muhammadiyah 1 Candi experienced several obstacles at the beginning of its implementation, namely the lack of parental education in using learning tools such as zoom meetings. From these obstacles, SD Muhammadiyah 1 Candi Provided solutions in the from of home visits and direct classes. Home visits are intended to provide more understanding to students. Direct class is a solution for students who do not have cellphones. However, during the application of online learning students are very enthusiastic in their teaching and learing activities.